Design fabrication and testing of ginner drier - DEVI, AJAYAMBIKA S. J; George Philip; Joby Bastian; Manuel, V. F (Tavanur Kelappaji College of Agricultural Engineering and Technology, 1990)
project report
project report
Keywords: project report